An incoherent feedforward loop interprets NFκB/RelA dynamics to determine TNF‐induced necroptosis decisions. Issue 12 (14th December 2020) - Oliver Metzig, Marie; Tang, Ying; Mitchell, Simon; Taylor, Brooks; Foreman, Robert; Wollman, Roy; Hoffmann, Alexander
Abstract: Balancing cell death is essential to maintain healthy tissue homeostasis and prevent disease. Tumor necrosis factor (TNF) not only activates nuclear factor κB (NFκB), which coordinates the cellular response to inflammation, but may also trigger necroptosis, a pro‐inflammatory form of cell death. Whether TNF‐induced NFκB affects the fate decision to undergo TNF‐induced necroptosis is unclear. Live‐cell microscopy and model‐aided analysis of death kinetics identified a molecular circuit that interprets TNF‐induced NFκB/RelA dynamics to control necroptosis decisions. Inducible expression of TNFAIP3/A20 forms an incoherent feedforward loop to interfere with the RIPK3‐containing necrosome complex and protect a fraction of cells from transient, but not long‐term TNF exposure. Furthermore, dysregulated NFκB dynamics often associated with disease diminish TNF‐induced necroptosis. Our results suggest that TNF's dual roles in either coordinating cellular responses to inflammation, or further amplifying inflammation are determined by a dynamic NFκB‐A20‐RIPK3 circuit, that could be targeted to treat inflammation and cancer. SYNOPSIS: Tumor necrosis factor (TNF) activates NFκB to counteract necrotic cell death. This study reveals that inducible A20 expression provides an incoherent feedforward loop that protects cells from transient, but not long‐lasting TNF exposure. Live‐cell imaging reveals two‐phased TNF‐induced necroptotic death kinetics. NFκB inducible A20 constitutes a noisy incoherent feedforward loop. A20 provides transient protection such that prolonged TNF still kills cells. Dysregulated NFκB dynamics may thus diminish pro‐inflammatory cell death. Abstract : Tumor necrosis factor (TNF) activates NFκB to counteract necrotic cell death. This study reveals that inducible A20 expression provides an incoherent feedforward loop that protects cells from transient, but not long‐lasting TNF exposure.